Promoção da saúde e prevenção de doenças na saúde suplementar: uma proposta de reorientação do modelo assistencial? - Andreza Trevenzoli Rodrigues (2013)
The objective of this study is to analyze health promotion programs in companies of private health insurance and their relationship with the care model practiced in the supplementary sector. It is a study of multiple cases of qualitative approach, supported in the methodological theoretical referential of the hermeneutics-dialectics. The methodological course included three stages: exploration, fieldwork and data comprehension. In the exploratory stage, the companies that develop programs of health promotion and prevention of diseases in Belo Horizonte-Minas Gerais were identified by searching on the ANS website. Seventy-nine companies were identified among them twenty-three confirmed the offer of programs and six accepted the invitation to participate in the study. The fieldwork consisted in interviews with managers of the companies and/or coordinators of programs, followed by outlying observation of the programs and interviews with professionals and involved beneficiaries. Thirteen programs were studied in depth. In these programs, the focus in prevention and control of obesity and incentive to the physical activity showed up. It was also outstanding the womens and elder's participation. The data comprehension was guided by the synthesis of crossed cases. The analysis clarified that the promotion and prevention programs in the supplementary sector are in a land of disputes. There are tensions among the logic that guide the approach of health promotion, the offer of programs, the access, the beneficiaries' responsibility and the political induction by ANS. The behavioral approach of the health promotion is prevalent in the study sceneries, which showed coherence with the ideals espoused in the private health sector. The results indicate the disciplinary character of the programs, which are developed starting from the bio-political device of habits regulation and life styles. In the organizational aspect, it was revealed the existence of difference between the companies, concerning the representativeness of the programs in their organizational structure. There are more institutionalized programs successful in relation to the continuity of the practices, others present tendency to vulnerability and discontinuity. Certainly the programs still occupy a secondary position compared to the amplitude of the services that comprise the technological arsenal used by the companies. These findings are opposed to the intense incentive of ANS, leading to the conclusion that there is a relative normative influence of the regulatory agency on the decisive processes of the companies, regarding the offer of programs. For the companies, the health promotion programs fulfill the interests of: make customers faithful, reduce costs or complementthe care strategies. We conclude that, despite the evident crossing of capital accumulation in the offer of health promotion in the supplementary sector, the analyzed programs indicate a new logic of health production in the field, which useslittle other spaces and professionals. Thus, the incorporation of health promotion on programs signals to the beginning of a change process in the health care model that, in order to achieve the level of transformation, requires higher investmentand other strategies that ensure community empowerment, social participation, holistic, union of sectors, equity and sustainability.